Zoonotic parasites in dog feces from Leon, Mexico - Hernandez Muñoz, Eduardo Alfonso; Martínez Canseco, Jesús; Beltrán-Rico, Ariadna; Hernández Tavera, Roberto; González Aguilera, Benjamín; Pérez González, Luis Braulio (Acta Universitaria, 2019)
Dogs are associated with at least 60 zoonotic diseases. Statistically, intestinal parasites stand out. The objective of this study is to evaluate the presence of zoonotic parasitic forms in dog feces collected from public parks and median strips in the city of Leon, México. Between June and August, 2015, dog feces were collected from 60 public parks and four median strips of the city. Samples were processed by the formalin-ether concentration technique and analyzed by optical microscopy. A total of 439 fecal samples from 64 areas were analyzed; the median of collected samples was 6 (Q1 to Q3: 2 to 12) per park. Contamination was present in 46 (71.88%) areas. It was identified that five (1.14%) areas tested positive for at least one parasite and one (0.23%) turned out positive for more than one parasite. The most common parasite was Ancylostoma spp, appearing in 3/439 samples (0.68%), among others. The rate of parks with fecal contamination was 71.88%, of which 10.87% showed parasitic contamination. Ancylostoma spp was the most prevalent parasite. Sanitary measures are needed to lower fecal contamination in public parks and the number of parasitized dogs.